The effects of Selenium phytotoxicity on two wheat (Triticum aestivum) cultivars differing in Se tolerance and the role of antioxidant enzymes in the tolerance mechanism - Gokbulut Tarik; Akbulut Mikail; Temizgul Ridvan (The EuroBiotech Journal)
Wheat seedlings were hydroponically grown in Hoagland solution containing various levels of Se. Tolerance response to Se toxicity was investigated by determining the level of thiobarbituric acid reactive substance (TBARS), proline and chlorophyll content, the growth parameters, and the activity of antioxidant enzymes. The toxic level of Se treatment significantly retarded the seedling growth. A substantial amount of proline accumulation was also observed in response to toxic Se concentration, but it was more pronounced in putative-sensitive cultivars. Chlorophyll content significantly decreased in Se-intoxicated seedlings and increased at the lowest Se dose in both cultivars. Severe and mild chlorosis was observed in putative-sensitive and tolerant cultivars at the highest Se level. Alterations in the activities of glutathione reductase (GR, 1.6.4.2), glutathione S transferase (GST, 2.5.1.18), guaiacol peroxidase (GPX, 1.11.1.7), catalase (CAT, 1.11.1.6), and ascorbate peroxidase (APX, 1.11.1.11) and superoxide dismutase (SOD, EC 1.15.1.1) were determined. TBAR level did not significantly increase in putative tolerant cultivars as an indicator of membrane lipid peroxidation. However, a significant increase was observed in putative-sensitive cultivars in response to higher selenium concentrations. In higher Se treatment groups, CAT and GST activities significantly increased in putative Se tolerant cultivars. However, excluding SOD, the activity of all the studied enzymes was increased considerably in putative-sensitive cultivars in a dose-dependent manner. Higher antioxidant enzyme activities and a substantial amount of proline accumulation did not significantly contribute to overcoming Se phytotoxicity in wheat seedlings grown in media supplemented with toxic selenium levels.